(untitled) (The Journal of Knowledge and Innovation, 2023)
The main objective of this study is to investigate the determinants of online purchase inten-tiones. The study examines the influence of the trust, convenience and service quality on the intention to make online purchases. A self-administered questionnaire was used to obtain cross-sectional data from 281 individuals residing in the Koshi Province of Nepal. The data were further examined with structural equation modelling. Amos 21 was utilised to analyse the collected data. The results demonstrate that trust has a positive and substantial influence on the intention to make online purchases. Furthermore, it is important to note that convenience and service quality significantly influence online purchase intention. The study builds upon existing research by examining the impact of trust, convenience and service quality on online purchase intention. Although the literature on this topic is still scant, it is gradually growing. The findings will be advantageous for marketers and regulators when formulating and executing policies aimed at enticing individuals to engage in online purchases.